Promising Technologies in the Field of Helminth Vaccines - Perera, Dilhan J.; Ndao, Momar (Frontiers in Immunology, 2021)
Helminths contribute a larger global burden of disease than both malaria and tuberculosis. These eukaryotes have caused human infections since before our earliest recorded history (ie: earlier than 1200 B.C. for Schistosoma spp.). Despite the prevalence and importance of these infections, helminths are considered a neglected tropical disease for which there are no vaccines approved for human use. Similar to other parasites, helminths are complex organisms which employ a plethora of features such as: complex life cycles, chronic infections, and antigenic mimicry to name a few; making them difficult to target by conventional vaccine strategies. With novel vaccine strategies such as viral vectors and genetic elements, numerous constructs are being defined for a wide range of helminth parasites, however it has yet to be discussed which of these approaches may be the most effective. With human trials being conducted, and a pipeline of potential anti-helminthic antigens, greater understanding of helminth vaccine-induced immunity is necessary for the development of potent vaccine platforms and their optimal design. This review outlines the conventional and the most promising approaches in clinical and preclinical helminth vaccinology.